2007
DOI: 10.1590/s0102-311x2007001100007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de medidas de controle de flebotomíneos no norte do Estado do Paraná, Brasil

Abstract: Sandfly captures from April 2001-September 2002 were compared to those from October 1996-September 1997 and October 1998-April 2000 AM. In 2001 average captures in 1996-1997and 1997-1998Numerosos trabalhos de controle de flebotomíneos têm dado um enfoque para o uso de inseticidas químicos em paredes de casas e anexos (abrigos de animais, silos) 3,4,5,6,7,8,9 , em ambientes silvestres 10,11,12 e impregnados em mosquiteiros 13,14,15,16,17 . Essas medidas apesar de atrativas não são permanentes 18 , além do que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
3
10
0
2
Order By: Relevance
“…As 25 , diminuindo no período de coletas deste trabalho (75,4% e 23,4%). Nos três primeiros períodos, a mudança nas proporções das referidas espécies ocorreu, possivelmente, devido ao impacto das alterações introduzidas no meio ambiente, visto que Nyssomyia neivai se adapta melhor nos ambientes com alto grau de antropia.…”
Section: Discussionunclassified
“…As 25 , diminuindo no período de coletas deste trabalho (75,4% e 23,4%). Nos três primeiros períodos, a mudança nas proporções das referidas espécies ocorreu, possivelmente, devido ao impacto das alterações introduzidas no meio ambiente, visto que Nyssomyia neivai se adapta melhor nos ambientes com alto grau de antropia.…”
Section: Discussionunclassified
“…Although some studies reported deltamethrin residual effects up to 9-12 months inside houses 13,19 , strong anti-feeding effects when applied to dogs as collars or topically, and repellent effects in impregnated bednets 7,8,9 , and pyrethroids as lambdacyalothrin reducing impact on Lu. longipalpis sand fly captures after focal or indoor applications 14,18 , there are many reports about the short or transient effects of fenitrothion 14 , cypermethrin 12 and deltamethrin as peridomestic sprayed insecticide 1,13,22,36 . Unfortunately the effects of insecticides for longer periods than 14 days could not be assessed in this study due to an abrupt change in the weather conditions that reduced the population; both in the intervention and the control group, but the results obtained were consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Impoverished living conditions, premature discontinuation and/or use in inappropriate periods and environmental risks of insecticide applications in natural environments are all factors hindering phlebotomine control (Teodoro et al 2007).…”
Section: Phlebotomine Controlmentioning
confidence: 99%
“…This suggests that the lack of information about VL among the public at large, and among health professionals in particular, is a major drawback in reducing the severity of this disease. An aggravating contributing factor is the disorganization of public agencies and the constant replacement of vector control specialists by health agents, what causes a shortage of qualifi ed staff for control work (Teodoro et al 2007).…”
Section: Insecticidal Plantsmentioning
confidence: 99%
See 1 more Smart Citation